Relationship of value of teeth color with skin color in Makassar tribe - Eri H. Jubhari; Wahipa Wiro; Sinaryanti Sinaryanti (Journal of Dentomaxillofacial Science, 2018)
Objective: This study aim to determine the relationship between teeth color value and skin color value of the Makassar tribe.Material and Methods: This observational analytic research employs cross-sectional study and purposive sampling methods, with 73 samples; held in May 2012 in Bontoramba, Jeneponto district, South Sulawesi, Indonesia. It uses the Vita-Lumina shade guide for teeth color tests and Garnier FD344110.122.007 for skin color tests.Results: The results show that the distribution of teeth colour value in respondents is mostly in the highest values (A1, B1, A2, B2 color) which were 71.2%, while the skin value is mostly in a dark skin color (78.1%). Data was analyzed by the chi-square test. It was found that teeth color value was not related to skin color value in the Makassar tribe (p>0.05).Conclusion: Skin color value was not an indicator in determining the teeth color in the Makassar tribe.